1997
DOI: 10.1075/eoc.1.2.03mae
|View full text |Cite
|
Sign up to set email alerts
|

Gestural Communication in Macaques

Abstract: Communication by facial expressions and body postures plays an important role in the social dynamics of macaques. Macaques use gestures to mediate both competitive and cooperative interactions with other group members. Gestures convey information on the emotional state of the sender and its impending behavior but can also be used to inhibit the behavior of another individual or to request its participation in specific activities such as grooming, agonistic support, mating or play. Although most gestures are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Similarly, Deaner, Khera, and Platt found that two males were strongly correlated in their ranked preference for specific faces (Deaner et al, 2005). To understand what social characteristics were most important, we used a model-free, cluster-based approach and found that monkeys that were viewed earlier and longer were more likely to have direct gaze and had redder sex skin, both of which are important visual cues for guiding social behavior (Vandenbergh, 1965; Maestripieri, 1997, 2005; Nunn, 1999; Waitt et al, 2003, 2006; Gerald et al, 2007; Birmingham et al, 2008a; Higham et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Deaner, Khera, and Platt found that two males were strongly correlated in their ranked preference for specific faces (Deaner et al, 2005). To understand what social characteristics were most important, we used a model-free, cluster-based approach and found that monkeys that were viewed earlier and longer were more likely to have direct gaze and had redder sex skin, both of which are important visual cues for guiding social behavior (Vandenbergh, 1965; Maestripieri, 1997, 2005; Nunn, 1999; Waitt et al, 2003, 2006; Gerald et al, 2007; Birmingham et al, 2008a; Higham et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The scalp-retraction display (SR; for description see Table 1) is performed exclusively in aggressive contexts in M. fuscata (Maestripieri, 1997). On the contrary, in Tonkean macaques the same display can be used as an invitation to play (Thierry et al, 2000).…”
Section: Lip-smacking (Ls)mentioning
confidence: 99%
“…Then, a human ‘intruder,’ often wearing a face mask to conceal their identity, enters the room and stands in profile making no eye contact with the monkey. This is considered to be an ambiguous cue since gaze aversion is a signal of subordination in macaques (Maestripieri, 1997). While the intruder stands in profile macaques tend to freeze [generally defined as maintaining a tense body posture with no movement or vocalization for at least 3 s in non-human primates (Kalin et al, 2004)].…”
Section: Introductionmentioning
confidence: 99%
“…After a predetermined amount of time, the intruder orients frontally to stare at the monkey [a signal of dominance and threat in Macaca spp. and most other non-human primates (Maestripieri, 1997)] for an equal amount of time. When stared at, monkeys typically exhibit a range of aggressive-defensive and fear behaviors, reflecting appropriate fight or flight responses (Kalin and Shelton, 2003).…”
Section: Introductionmentioning
confidence: 99%